2013
DOI: 10.1530/rep-13-0178
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria functionality and sperm quality

Abstract: Although mitochondria are best known for being the eukaryotic cell powerhouses, these organelles participate in various cellular functions besides ATP production, such as calcium homoeostasis, generation of reactive oxygen species (ROS), the intrinsic apoptotic pathway and steroid hormone biosynthesis. The aim of this review was to discuss the putative roles of mitochondria in mammalian sperm function and how they may relate to sperm quality and fertilisation ability, particularly in humans. Although paternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
355
1
19

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 452 publications
(384 citation statements)
references
References 116 publications
9
355
1
19
Order By: Relevance
“…This staining is used to evaluate the ability of the mitochondria to produce ATP, which sustains the activity of spermatozoa and is thus positively correlated both with cellular motility and viability (GARNER et al, 1997). In addition, mitochondrial activity is related to Ca 2+ homeostasis and to the production of reactive oxygen species (ROS) that, at controlled levels, are part of the physiological events associated with fertilization (AMARAL et al, 2013). In the present study, the addition of lipids had no effect on mitochondrial activity in bovines or in equines.…”
Section: Discussionmentioning
confidence: 99%
“…This staining is used to evaluate the ability of the mitochondria to produce ATP, which sustains the activity of spermatozoa and is thus positively correlated both with cellular motility and viability (GARNER et al, 1997). In addition, mitochondrial activity is related to Ca 2+ homeostasis and to the production of reactive oxygen species (ROS) that, at controlled levels, are part of the physiological events associated with fertilization (AMARAL et al, 2013). In the present study, the addition of lipids had no effect on mitochondrial activity in bovines or in equines.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, peroxides have been associated with formation of the mitochondrial capsulea coat surrounding sperm mitochondria providing protection against possible proteolytic degradation [54]. It is suggested that during spermatogenesis peroxides may oxidize the active form of phospholipid hydroperoxide glutathione peroxidase (PHGPx), creating an intermediate that subsequently interacts with thiol groups to form a seleno-disulfide bond.…”
Section: Sperm Maturationmentioning
confidence: 99%
“…Mitochondria require such protection as their proper function is crucial for metabolism, cell cycle control and oxidative balance [51,53,54].…”
Section: Sperm Maturationmentioning
confidence: 99%
See 2 more Smart Citations